Türken- und Türkeibilder im 19. und 20. Jahrhundert Pädagogik, Bildungspolitik, Kulturtransfer - Lohmann, Ingrid; Böttcher, Julika (Wie die Türken in unsere Köpfe kamen. Eine deutsche Bildungsgeschichte, 2021)
Stereotypes are always riddled with prejudice, including the images people have of Turks and Turkey. Since they often originate from long-forgotten times, they persist all the more stubbornly in the collective unconscious. This volume reconstructs narratives, i.e. narrative forms of the discourse on Turks and Turkey, which have accumulated in recent educational history: Did they change over time? Or did outdated stereotypes simply continue to have an effect? The contributions use transnational and postcolonial perspectives to illuminate a chapter of educational history that is unknown today and aim to question the self-image of those working in education.